2015
DOI: 10.1177/2165079915589685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-Week Outdoor Brisk Walking Program on Fatigue in Hi-Tech Industry Employees

Abstract: Over 73% of hi-tech industry employees in Taiwan lack regular exercise. They are exposed to a highly variable and stressful work environment for extended periods of time, and may subsequently experience depression, detrimental to workers' physiological and mental health. In this cross-sectional survey, the authors explored the effect of an 8-week brisk walking program on the fatigue of employees in the hi-tech industry. The participants, from a hi-tech company in northern Taiwan, were randomly assigned to an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…In a randomized, cross-over trial, it was shown that the use of sit-stand desks reduced time spent sitting at work by 21 % while increasing energy and overall sense of well-being, and decreasing fatigue, with no impact on productivity [25]. A recent 8-week brisk walking intervention in sedentary employees of a high-tech company improved subjective fatigue, motivation and concentration [27], further showing that such interventions are feasible in ‘real world’ settings and provide similar beneficial effects on overall well-being as those observed in laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, cross-over trial, it was shown that the use of sit-stand desks reduced time spent sitting at work by 21 % while increasing energy and overall sense of well-being, and decreasing fatigue, with no impact on productivity [25]. A recent 8-week brisk walking intervention in sedentary employees of a high-tech company improved subjective fatigue, motivation and concentration [27], further showing that such interventions are feasible in ‘real world’ settings and provide similar beneficial effects on overall well-being as those observed in laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Their geographic origins were Australia (three articles, 30%), Taiwan and Korea (two articles, 20%), the USA (two articles, 20%), Ukraine, Sweden and the UK (one article for each, for a total of three articles, 30%). The sample size varied from 6 participants to 203883 participants [48][49][50][51][52][53][54][55][56][57]. Two studies included different age classes of participants: 2-4, 5-18 or more than 18 years [52]; children, adult and senior [50].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Berdasarkan 9 artikel yang telah dianalisis, beberapa manfaat yang telah terbukti efektif berdasarkan evidence based adalah untuk mengurangi tingkat kelelahan terutama pada pasien dengan kanker payudara yang menjalani kemoterapi (19) dan para pekerja industri tingkat tinggi (22). Mengurangi risiko kardiovaskular pada pasien, efektif mengurangi kadar gula darah (20) (12), efektif menurunkan tekanan darah terutama pada latihan intensitas tingkat sedang (26).…”
Section: Efektivitas Brisk Walkingunclassified